Gerakan Literasi Madrasah Sebagai Upaya Menumbuhkan Minat baca Siswa Madrasah Tsanawiyah - Madkan, Madkan; Haidar, M. Ali; Mumtahana, Lusia (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2022)
Writing this article aims to analyze and describe the strategy of the Madrasah Literacy Movement (GLM) to foster reading interest among MTs students. Ma'arif Daruttaqwa. This study uses a qualitative method with a case study approach, data collection through interviews, and documents. data analysis using the Miles and Huberman model, namely data reduction, data display and conclusion verification. The results of this research are strategies to increase students' interest in reading including 1. Program 15 reading before learning begins. 2. Improvement of the library and procurement of textbooks and non-learning. 3. Motivation from administrators and teachers and the surrounding environment. Besides the three things above, giving assignments to students is also able to foster interest in reading in madrasah students.